Credit risk: Evidence in Ecuadorian banking system - Urbina Poveda, Myriam (2019)
Using data from the Ecuadorian private banking system for the period 2000-2017, this paper analyses macroeconomic and bank specific variables as determinants of credit risk, evaluated through a panel data with random effects. The findings highlight that macroeconomic and financial conditions of the country can explain credit banks quality in Ecuador. In particular, the factors that influence the credit risk in private banking system are the unemployment, government variables, the growth rate of loans, provisions, profitability and size. DOI: https://doi.org/10.31164/bcoyu.23.2019.842 URL: http://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/842